Correlation Between Pulmonary Sclerosing Pneumocytoma Features and MSCT Imaging Manifestations in 34 Patients: Implications for Precision Medicine - Xu, Gen; Wang, Zhaoyu; Xiong, Zeng; Li, Manqiu; Luo, Weijun; Xu, Yong; Min, Tang (Frontiers in Medicine, 2021)
Objective: To identify and analyze the multi-slice computed tomography (MSCT) imaging manifestations and clinicopathological features of PSP to improve the preoperative and intraoperative diagnosis of the disease. Method: This was a retrospective study conducted on the imaging and clinicopathological data of the PSP patients treated in two major hospitals in China from October 2001 to December 2019. The locations of lung lesions, clinical symptoms, surgical complications, MSCT imaging features, and the corresponding relationship with clinicopathological features were assessed. Then, a new diagnostic approach was defined and used to train imaging and pathological doctors (experimental group). Then, the diagnostic accuracy of the experimental group was evaluated in preoperative and intraoperative diagnosis of PSP. Results: Thirty-four PSP cases were analyzed (mean: 51.42; range: 39–69 years old). The peripheral type was more common, while 92% of the lesions located in the middle lobe of the right lung and the lower lobe of bilateral lungs. The shortest lesion edge-pleura distance ranged 0 to 30 mm and 46% of the lesions (16/34) were attached to the pleura, 62% (21/34) located at 0–5 mm, 92% (31/34) within 20 mm from the pleura. Diameters of the lesions ranged 8.58 to 68.41 mm, while most of them were 20-40 mm. All lesions showed enhancement, and 97% (33/34) were unevenly enhanced. PSP volume was negatively correlated with the total degree of enhancement (r = −0.587, p < 0.01), and the volume difference between the obvious enhancement zone and the slight enhancement zone (r = −0.795, p < 0.01). Welt vessel sign was observed in 61.7% (21/34) of cases, and none of welt vessels entered into the lesions. Vascular-like enhancement area inside the lesion showed no significant correlation with the welt vessels outside the lesion, and no case showed entrance of bronchus into the lesion. The trained experimental group showed significantly greater diagnostic accuracy than the control group. In particular, the accuracy rate of intraoperative frozen section diagnosis was 60% higher in the experimental group than the control group. Conclusion: PSP has characteristic imaging manifestations, which can be utilized to improve the preoperative and intraoperative diagnostic coincidence rate of PSP.